Young‐onset colorectal cancer: Insights from an English population‐based study. (4th May 2022) - Franklyn, Joshua; Lomax, Joe; Labib, Peter L. Z.; Baker, Amy; Balasubramanya, Supriya; Natale, Joe; Abdalkoddus, Muhammad; Hosking, Joanne; Coleman, Mark G.; Smolarek, Sebastian
Abstract: Aim: Young colorectal cancer (CRC) patients are reported to have more aggressive disease, an advanced stage at diagnosis and conflicting survival outcomes. The aim of this study was to analyse the demographics, clinicopathological features and prognosis of young CRC at a population‐based level in England. Method: This is a retrospective review of all CRC patients using data from Public Health England collated from regional cancer registries in England between 2010 and 2014. Those aged 40 years and below were classified as young and those over 40 were classified as older. Results: Overall, 167, 501 patients had CRC. Of these, 3757 patients (2.2%) were young. Right‐sided cancers were more common in younger patients (48.2% vs. 32.9%, p  < 0.001). Favourable histological grade (well or moderately differentiated) was present in 83.1% and 73.5% of young and older patients, respectively. The percentage of young and older patients being diagnosed at an early stage (Stages 1 and 2) was similar at 40.6% vs. 42.9%. The 5‐year age‐ and gender‐adjusted relative survival (cancer specific) was significantly better for young patients when compared with older patients diagnosed with CRC. Additionally, overall 5‐year survival was better for younger patients (71.6% and 47.2%, p  < 0.001 in young and older CRC patients respectively). Conclusion: The increased right‐sided colon cancer in young CRC patients in England warrants attention. Contrary to previous reports, they do not present at later stage. Young CRC patients have better overall and relative survival than older patients with CRC.